A Way to Learn - Technical Vocabulary through Multimedia Based on Viewing TV Series. - Seo, Jiyoung (Lupa empresarial, 2016)
Since movies and TV series have been widely used in the English language classroom, many educational methodologies have been suggested. It is no surprise that teachers and learners all welcome the idea of using movies or TV series in the ESL/EFL classroom as such material includes many practical expressions and it brings enjoyment. However, it can also bring disappointment if teachers do not know how to teach the practical expressions leading to learners feeling bored. In the study on the selection of movies, Lee (2000) asserted that three criteria need to be considered in selecting films: 1) popular and current movies, 2) movie scripts with interesting and usable English language, and 3) movie lines that contain typical conversation styles of English speakers. As such, TV programs such as Blacklist or NCIS are hardly used in ELT, although, in some cases, they are popular because of their difficult technical vocabulary and conversations that are unlikely to happen in the real world. Despite the little concern about technical vocabulary, a lot of research supports the idea that learning such vocabulary is beneficial, and even essential in the field of ESP (Chung & Nation, 2004). Gablasova (2014) stated that technical vocabulary and knowledge of the subject are closely linked. Studying an academic subject is a process in which the students’ knowledge of a certain field is broadened or deepened while they simultaneously acquire words for the new concepts they learn (Mohan & van Naerssen, 1997). As a result, learning the meanings of new specialized words is an integral part of learning a new subject (Bravo & Cervetti, 2009; Woodward–Kron, 2008). Moreover, the appropriate use of technical words can be an indicator of the depth of subject knowledge (Drum & Konopak, 1987) and can thus serve as a basis for the assessment of subject competence. Webb and Rogers (2009) indicate that “materials which provide visual and aural input such as movies may be conducive to incidental vocabulary learning.” Hulstijn (2001, p. 271) defined technical vocabulary as “learning of vocabulary as the by-product of any activity not explicitly geared to vocabulary learning.” In other words, “rigor mortis” can be learned while watching a medical TV series. Movies that include a lot of technical vocabulary are called ‘discipline-related movies (Csomay & Petrovic, 2012).’ Watching a TV series makes incidental learning possible. That is, after watching a TV series such as House or Grey’s Anatomy, we might incidentally become familiar with medical procedures and treatment of illness. Technical vocabulary does not just function in a particular field; it can also play an important role in general English learning. In fact, to use movies or TV dramas as material, means to memorize utterances from them. What is needed here is to theoretically explain why memorizing such utterances is necessary for better language learning. Therefore, this paper will focus on the relationship between technical vocabulary and language development.